Study on Existing Status of Farm Environment and Awareness in a Farming Community of Dinajpur District - Arfin, A; Baten, MA; Nahar, BS; Sattar, MA (Journal of Environmental Science and Natural Resources, 2012)
The main purpose of this study was to investigate the existing status and activities of the farmers in a farming community and also to evaluate the level of knowledge and awareness of the farmers on environmental degradation. From the findings of results and discussion it was observed that the illiteracy rate was higher (45%) in small farmers compared to medium (30%) and large (25%) farmers. The percentage of knowledge and awareness of the large farmers about soil organic matter depletion was about 80%. In case of the small farmers about 85% were unaware about soil organic matter depletion. Findings also indicated that 80% of the large farmers had awareness about the impact of soil organic matter depletion while 85% of the small farmers were not aware about the impact of soil organic matter depletion and 70% of the medium farmers had awareness. Findings also indicated that 25% of the large farmers, 15% of the medium farmers and 10% of the small farmers had knowledge about the application of excess chemical fertilizer and 50% of them did not response. Thirty five percent of the large farmers, 25% of the medium farmers and 10% of the small farmers had knowledge that due to the effect of pesticide diseases occurred on human health and 30% of them did not response. Twenty percent of the large farmers, 10% of the medium farmers and 5% of the small farmers had knowledge about the preservation techniques of soil quality and 65% of them did not response. It was also found that out of the four independent variables i.e. age, level of education, occupation and farm size had positive significant relationship with environmental awareness. DOI: http://dx.doi.org/10.3329/jesnr.v4i2.10166 J. Environ. Sci. & Natural Resources, 4(2): 151-154, 2011